ANALISIS PERUBAHAN KERAPATAN TANAMAN MANGROVE TERHADAP PERUBAHAN GARIS PANTAI DI KABUPATEN PATI DENGAN METODE PENGINDERAAN JAUH DAN APLIKASI DIGITAL SHORELINE ANALYSIS SYSTEM (DSAS) TAHUN 2017-2020 - Thia Prahesti; Nurhadi Bashit; Yasser Wahyuddin (Department of Geodesy Engineering, Faculty of Engineering, Diponegoro University,Indonesia, 2020)
Pati Regency has a coastline of 60 km with a characteristic muddy beach. The coastal community in Pati Regency is very dependent on coastal and marine products, so it needs to be preserved. A decrease in coastal environment quality can be indicated by looking at the mangrove of quality plants. The Government of Pati Regency carries out regular mangrove planting to improve the quality of life in the coastal environment, but there is no supervision. This study uses remote sensing technology and GIS to determine the relationship between changes in mangrove plant density and changes in coastlines in Pati Regency from 2017 to 2020. This study uses remote sensing methods using the NDWI water index transformation method to determine the shoreline from Sentinel-2-year image. 2017-2020, MSL reduction using DEMNAS and MSL, then processed with a Geographical Information System using DSAS to obtain the results of shoreline changes (NSM) as well as guided classifications for land cover and vegetation indexes NDVI and GNDVI which are used to map mangrove vegetation density on the coast of the Pati Regency. The results showed that the average change in the coastline in Pati Regency has increased by 22,260 m. Changes in the area of mangroves on the coast of Pati Regency have increased by 86.634 hectares. The results also showed that the relationship between changes in mangrove density and shoreline changes on the coast of Pati Regency used simple linear regression with the coefficient of determination (R2) of 0,089 and the correlation coefficient (R) of 0,299. These results indicate a correlation enough. The calculation of the F test to determine changes in mangrove density with changes in shoreline has a significant effect, so that if the value of mangrove density is higher, changes in shoreline will tend to increase (accretion).